Evaluasi Kinerja Pemerintah Provinsi dalam Penyaluran Insentif dan Santunan Kematian bagi Tenaga Kesehatan - Marihot Nasution (Pusat Kajian Anggaran, 2021)
This study evaluates performance in the distribution of incentives and death benefits for health workers during the Covid-19 pandemic in the 2020 fiscal year. The evaluation was carried out by the provincial government in Indonesia by collecting data on the results of the BPK examination on the effectiveness of handling Covid-19 in the health sector by the government province. The results of the evaluation show that in the distribution of incentive funds and death compensation for health workers, several provincial governments are late in distributing funds to health workers and the distribution of incentive funds is not in the right amount. This condition is caused by the provincial government waiting for clarity on the reference for the disbursement of funds issued by the Ministry of Health. The reference for disbursement of funds in the form of technical guidelines summarized in the Decree of the Minister of Health has changed in a relatively short time and has not been synergistic with regulations from other ministries so there are overlapping regulations and misinterpretations by local governments. The Ministry of Health also did not confirm the reporting of the distribution of funds for incentives and death benefits, so that the monitoring and evaluation process did not run.